Overexpression of UbcH10 alternates the cell cycle profile and accelerate the tumor proliferation in colon cancer - Hatoh Shinji; Taira Naruto; Ikeda Hirokuni; Fujita Takeo; Naito Minoru; Doihara Hiroyoshi (BMC Cancer, 2009)
Abstract Background UbcH10 participates in proper metaphase to anaphase transition, and abrogation of UbcH10 results in the premature separation of sister chromatids. To assess the potential role of UbcH10 in colon cancer progression, we analyzed the clinicopathological relevance of UbcH10 in colon cancer. Methods We firstly screened the expression profile of UbcH10 in various types of cancer tissues as well as cell lines. Thereafter, using the colon cancer cells line, we manipulated the expression of UbcH10 and evaluated the cell cycle profile and cellular proliferations. Furthermore, the clinicopathological significance of UbcH10 was immunohistologically evaluated in patients with colon cancer. Statistical analysis was performed using the student's t-test and Chi-square test. Results Using the colon cancer cells, depletion of UbcH10 resulted in suppression of cellular growth whereas overexpression of UbcH10 promoted the cellular growth and oncogenic cellular growth. Mitotic population was markedly alternated by the manipulation of UbcH10 expression. Immunohistochemical analysis indicated that UbcH10 was significantly higher in colon cancer tissue compared with normal colon epithelia. Furthermore, the clinicopathological evaluation revealed that UbcH10 was associated with high-grade histological tumors. Conclusion The results show the clinicopathological significance of UbcH10 in the progression of colon cancer. Thus UbcH10 may act as a novel biomarker in patients with colon cancer.